Pengaruh Budaya Organisasi dan Motivasi terhadap Kinerja Karyawan Perum Bulog Kantor Cabang Medan - Ahmad Prayudi; Warsani Purnama Sari (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the influence of Organizational Culture and Motivation on the Employee Performance at Perum BULOG, Medan Branch Office. A quantitative method with an associative approach was employed. The population consisted of employees at Perum BULOG, Medan Branch Office, and a saturated sampling technique was used, resulting in a sample of 36 respondents. Data were collected by distributing questionnaires to respondents who met the study's criteria. The data were processed using SPSS software, and the analysis techniques included multiple linear regression, the t-test (partial), and the F-test (simultaneous). Validity testing was conducted using the Statistical Package for the Social Sciences (SPSS) program. Questionnaires were administered to 36 employees of Perum BULOG, Medan Branch Office. Partial test results (t-test) indicate that the Organizational Culture variable has a positive and significant effect on Employee Performance. Similarly, the Motivation variable has a positive and significant effect on Employee Performance. Simultaneous testing (F-test) shows that both independent variables have a significant effect on the dependent variable. The Adjusted R-Square value is 0.516, or 51.6%, indicating that 51.6% of the variation in Employee Performance (Y) can be explained by Organizational Culture (X1) and Motivation (X2), while the remaining 48.4% is explained by factors not examined in this study.